Die im Nachfeld stehenden Sätze mit Spitzenstellung des finiten Verbs - Wiktorowicz, Józef (Studia Germanica Posnaniensia, 2018)
The paper discusses causal clauses in contemporary German, positioned after the main clause, which lack a conjunction combining it with that clause. Their characteristic feature is the initial position of the predicate and the obligatory use of the particle doch. Numerous grammars either ignore such causal clauses or consider them obsolete, although they are found not only in literary but also in colloquial speech texts.